CFD simulation of dynamic characteristics of a solenoid valve for exhaust gas turbocharger system. (5th January 2017) - Li, Shiyang; Wu, Peng; Cao, Linlin; Wu, Dazhuan; She, Yantao
Highlights: Dynamic characteristics of a PWM-controlled solenoid valve are investigated. Transient CFD simulations with dynamic mesh technique are conducted. Subsonic and sonic flow structures are visualized and analyzed in detail. Mean control pressures obtained from CFD are verified by experimental data. Pressure wave transmission during valve opening process is captured. Abstract: The transient flow and dynamic characteristics of a PWM-controlled solenoid valve are simulated by CFD to investigate the pressure control performance of the solenoid valve under PWM-controlled conditions. A group of cases with a constant valve opening but different pressure drops are used in the steady-state CFD simulations, which cover both sonic and subsonic flows. The mass flow rates obtained from CFD simulations are compared with theoretical results and show a good agreement, indicating that CFD is capable of handling the complex flows. The dynamic mesh technique is used to simulate the movement of the valve spool, and transient CFD simulations are conducted to analyze the dynamic characteristics. The responses of the control pressure and the mass flow rate to the duty-cycle variation are analyzed for 30%, 50%, and 80% duty cycles. The mean control pressure values are verified by experimental data. The flow force exerted on the spool is recorded and the transient force is compared with the steady force. The pressure wave transmission during the valve opening process is captured. The influence of the valve opening time on the control pressure is also investigated, and results show that the former can affect the mean control pressure.